LOX-1, OxLDL, and Atherosclerosis - Angela Pirillo; Giuseppe Danilo Norata; Alberico Luigi Catapano (Hindawi Limited, 2013)
Oxidized low-density lipoprotein (OxLDL) contributes to the atherosclerotic plaque formation and progression by several mechanisms, including the induction of endothelial cell activation and dysfunction, macrophage foam cell formation, and smooth muscle cell migration and proliferation. Vascular wall cells express on their surface several scavenger receptors that mediate the cellular effects of OxLDL. The lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is the main OxLDL receptor of endothelial cells, and it is expressed also in macrophages and smooth muscle cells. LOX-1 is almost undetectable under physiological conditions, but it is upregulated following the exposure to several proinflammatory and proatherogenic stimuli and can be detected in animal and human atherosclerotic lesions. The key contribution of LOX-1 to the atherogenic process has been confirmed in animal models; LOX-1 knockout mice exhibit reduced intima thickness and inflammation and increased expression of protective factors; on the contrary, LOX-1 overexpressing mice present an accelerated atherosclerotic lesion formation which is associated with increased inflammation. In humans, LOX-1 gene polymorphisms were associated with increased susceptibility to myocardial infarction. Inhibition of the LOX-1 receptor with chemicals or antisense nucleotides is currently being investigated and represents an emerging approach for controlling OxLDL-LOX-1 mediated proatherogenic effects.